Determinants of submaximal exercise capacity in patients at risk for heart failure with preserved ejection fraction—results from the DIAST‐CHF study. (27th April 2015) - Stahrenberg, Raoul; Duvinage, André; Mende, Meinhard; Gelbrich, Götz; auf der Heide, Wiebke; Düngen, Hans‐Dirk; Binder, Lutz; Nolte, Kathleen; Herrmann‐Lingen, Christoph; Hasenfuß, Gerd; Pieske, Burkert; Wachter, Rolf; et al.
Abstract Objectives and Background The aim of this study was to identify determinants of submaximal exercise capacity as measured by 6 min walking distance in patients at risk for heart failure with preserved ejection fraction (HFpEF). Methods A cross‐sectional analysis from the prospective cohort programme Prevalence and Clinical Course of Diastolic Dysfunction and Heart Failure (DIAST‐CHF) that included a total of 1937 patients (age, 50–85 years) with >1 risk factor (hypertension, atherosclerotic disease, diabetes mellitus, and obstructive sleep apnoea) was carried out. Besides comprehensive clinical phenotyping, standardized 6 min walk test and state‐of‐the‐art echocardiography were performed, and blood samples for biomarker assessment were obtained. Patients with an ejection fraction <50% or without evaluable exercise test were excluded from this analysis. Results One thousand three hundred eighty‐seven patients fulfilled all criteria for this analysis. In the univariate analysis, 6 min walk distance was inversely related to E/e′ values (P < 0.001). In the multivariate analysis, 6 min walk distance decreased significantly with age, female sex, increasing body mass index, diabetes, chronic obstructive lung disease, and peripheral artery disease. However, the association of 6 min walk distance with resting parameters of diastolic function was significantly attenuated with multivariate regression. In contrast, mid‐regional pro‐adrenomedullin, mid‐regional pro‐atrial natriuretic peptide, and N‐terminal pro‐B‐type natriuretic peptide were independently associated with submaximal exercise capacity when added to the base model (all P < 0.001). Conclusions Classical risk factors for heart failure and neuroendocrine activation are independently associated with sub‐maximal exercise capacity, while diastolic function parameters obtained at rest were not. This observation substantiates the role of co‐morbidities as relevant contributors to the clinical picture of HFpEF and the limitation of resting indices of diastolic function for diagnosing HFpEF.